Corrigendum to “Algorithm for sizing parabolic-trough solar collectors” [Therm. Sci. Eng. Prog. 24 (2021) 100932] (Thermal Science and Engineering Progress (2021) 24, (S2451904921000949), (10.1016/j.tsep.2021.100932)) - Nascimento, Fernanda I. [UNESP]; Zavaleta-Aguilar, Elí W. [UNESP]; Simões-Moreira, José R. (Elsevier, 2021)
The authors regret to inform that the following corrected text should be considered: - Page 3, right column, line 16: … 70° and 110° [22]… - Page 3, right column, line 25: … reaches the receiver [23,37]… - Page 3, right column, line 26: … greater than 0.90 [21]… Also, the correct Fig. 3 is:[Figure presented] Fig. 3. PTC sizing algorithm flowchart scheme. The authors would like to apologise for any inconvenience caused.